Do health trajectories predict neighborhood outcomes? Evidence of health selection in a diverse sample of U.S. adults. (January 2022) - Rolheiser, Lyndsey; Zacher, Meghan; Subramanian, S.V.; Arcaya, Mariana C.
Abstract: Across the United States, residents of lower income neighborhoods evince poorer health, on average, than residents of more affluent areas. Studies aiming to explain this pattern have focused largely on the effects of neighborhood characteristics on residents' health, often overlooking the possibility that the reverse causal process—that a person's health impacts where they live, or "health selection into neighborhoods"—also plays a role. We investigated processes of health selection using the Panel Study of Income Dynamics, a longitudinal survey of U.S. households. Using ordinary least squares linear regression, we estimated the effect of householders' self-rated health on their neighborhood socioeconomic status (SES, the Census tract-level family poverty rate) in 2013, adjusting for neighborhood SES and health in 2001 as well as sociodemographic characteristics and residential mobility. Poorer health was associated with residence in higher poverty neighborhoods overall. Stratified models indicated that while health selection was observed across both race/ethnicity and class boundaries, the relationship between poor health and neighborhood poverty was stronger among non-Hispanic Black respondents, those with low income, and respondents who either moved moderate distances or did not move at all during the study period. We conclude with a call for future work exploring the mechanisms leading those in worse health to reside in higher poverty neighborhoods, and for public health policies that seek not only to improve health supporting conditions in economically disadvantaged neighborhoods, but that also support the economic and social needs of residents struggling with health problems. Highlights: One of the first studies to examine health selection in a heterogeneous U.S. sample and in several key population subgroups Find evidence of an association between poor health and residence in higher poverty neighborhoods after adjusting for previous neighborhood socioeconomic status and health and sociodemographic characteristics Find evidence of health-based selective mobility and suggestive evidence of health-based selective immobility